In pursuit of privilege : a history of New York City's upper class & the making of a metropolis - Hood, Clifton (Columbia University Press, 2017)
"Clifton Hood traces the history of the elite class of New York City and the institutions they created in their relentless pursuit of privilege. While they were responsible for the creation of intuitions such as Columbia University, the New York Public Library system, and the Metropolitan Museum of Art, and provided skilled leadership in eras of immense turmoil, the idea of a privileged class clashes with the American democratic ideal. And, in fact, this upper class clashed with the rising professional class of bankers, lawyers, and other executives who increasingly rose in prestige and power as time rolled on. In Pursuit of Privilege traces the history of this elite class over two centuries, focusing on decades of upheaval and great change (such as the wars of the 1780s, 1860s, 1940s and the urban upheaval in the 1820s and 1970s), and argues the upper class was not born in the Gilded Age, but that the late nineteenth century was one of many periods where the elites wielded great power and influence and profoundly shaped, for better and for worse, the history of New York and America."--Provided by publisher